The role of Re in improving the oxidation-resistance of a Re modified PtAl coating on Mo-rich single crystal superalloy. (1st December 2020) - Li, Jingchen; Wei, Liangliang; He, Jian; Chen, Hao; Guo, Hongbo
Highlights: A novel Re modified β-(Ni, Pt)Al coating was prepared on single-crystal superalloy with high amount of Mo. The high temperature oxidation-resistance was improved by the addition of Re to traditional β-(Ni, Pt)Al coatings. The outward diffusion of Mo was effectively inhibited by Re to form σ-MoRe phases. Abstract: A novel Re modified β-(Ni, Pt)Al coating was prepared on a Mo-rich Ni3 Al-based single crystal (SC) superalloy by electro-deposition of Re/Pt dual films and low-activity aluminizing. The isothermal oxidation behavior of the Re modified β-(Ni, Pt)Al coating and traditional β-(Ni, Pt)Al coating was comparatively studied at 1100 °C. Apparent spallation of oxide scale was found on the surface of traditional β-(Ni, Pt)Al coating after 300 h isothermal exposure, which mainly resulted from the evaporation of Mo-containing oxides. It is further found that the outward diffusion of Mo from the SC substrate was effectively inhibited in the Re modified β-(Ni, Pt)Al coating by forming the σ-MoRe phase both at the coating/superalloy interface and grain boundaries. It is also revealed that the addition of Re can stabilise Mo to form the σ-MoRe phase, allowing the improved oxidation resistance of the Re modified β-(Ni, Pt)Al coating.